Somatic Mutations in Oncogenes Are in Chronic Myeloid Leukemia Acquired De Novo via Deregulated Base-Excision Repair and Alternative Non-Homologous End Joining - Curik, Nikola; Polivkova, Vaclava; Burda, Pavel; Koblihova, Jitka; Laznicka, Adam; Kalina, Tomas; Kanderova, Veronika; Brezinova, Jana; Ransdorfova, Sarka; Karasova, Dominika; Rejlova, Katerina; Bakardjieva, Marina; et al. (Frontiers in Oncology, 2021)
Somatic mutations are a common molecular mechanism through which chronic myeloid leukemia cells acquire resistance to tyrosine kinase inhibitors therapy. While most of the mutations in the kinase domain of BCR-ABL1 can be successfully managed, the recurrent somatic mutations in other genes may be therapeutically challenging. Despite the major clinical relevance of mutation-associated resistance in chronic myeloid leukemia, the mechanisms underlying mutation acquisition in tyrosine kinase inhibitors-treated leukemic cells are not well understood. This work demonstrated de novo acquisition of mutations on isolated single-cell sorted chronic myeloid leukemia clones growing in the presence of imatinib. The acquisition of mutations was associated with the significantly increased expression of the LIG1 and PARP1 genes involved in the error-prone alternative nonhomologous end-joining pathway, leading to genomic instability, and increased expression of the UNG, FEN and POLD3 genes involved in the base-excision repair (long patch) pathway, allowing point mutagenesis. This work showed in vitro and in vivo that de novo acquisition of resistance-associated mutations in oncogenes is the prevalent method of somatic mutation development in chronic myeloid leukemia under tyrosine kinase inhibitors treatment.